A review of cryogenic cooling in high speed machining (HSM) of mold and die steels - Ahmad-Yazid, A.; Taha, Z.; Almanar, I.P. (Academic Journals, 2010)
Metal cutting generates heat which influences the quality of a finished product, the force needed in cutting as well as limiting the life of the cutting tool. There are various attempts by researchers all over the world to understand the mechanism and theory behind the temperature built-up during machining in order to achieve optimized machining procedure and best workpiece results. Theories are developed, experiments conducted as well as models and simulations proposed. The latest attempt in metal cutting cooling is through the use of chilled air, cryogenic cooling. A Ranque-Hilsch vortex tube (RHVT), a device with no moving parts, is used for this low-cost refrigeration purpose. Backgrounds of RHVT, various studies conducted on it, its performance and applications are discussed for the high speed metal cutting cooling application for mold and die steels. Option for future research is proposed.